Incidence of Intestinal Parasites in Government and Private School Going Children - Mishra, Kritika; Maharjan, Freeda; Chitrakar, Reshma; Chhetri, Nikita; Shrestha, Monica; Chaudhary, Richa; Chaturwedi, Shashi Bhushan (Tribhuvan University Journal of Microbiology, 2020)
Objective: Aim to assess the incidence of intestinal parasites in government and private school going children. Methods: The work was conducted from October, 2018 to March, 2019 at Microbiology Laboratory of DAV College, Dhobighat, Lalitpur. A total of 100 stool samples of children aged between 5-12 years were collected from both government and private schools situated in Lalitpur metropolitan city, during school hours. The stool samples were examined for intestinal parasites by Saline wet mount; Iodine wet mount and Formal – ether sedimentation technique. The questionnaires accompanying the queries related to the study were filled. Results: Of the total 100 stool samples examined, intestinal parasites were observed in 7% (7/100) of the total stool samples. Among the positive stool samples, 71% (5/7) of the stool samples were from government school’s children whereas 29% (2/7) were from private school’s children. Fifty seven percentage 57% (4/7) girls and 43% (3/7) boys were found to be infected with intestinal parasite in the tested stool samples. Out of total parasite detected, 57% (4/7) were eggs of Ancylostoma duodenale, 29% (2/7) were eggs of Ascaris lumbricoides and 14% (1/7) were cysts of Giardia lamblia. The study indicates that Ancylostoma is the most commonly infecting parasite followed by Ascaris and Giardia. Conclusion: Personal hygiene and sanitary condition were responsible for the incidence of intestinal parasites in the school going children. Environmental sanitation improvement and health education promotion will be helpful to reduce the parasitic infection rate.